If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 11x = 12x Solving 5 + 11x = 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 5 + 11x + -12x = 12x + -12x Combine like terms: 11x + -12x = -1x 5 + -1x = 12x + -12x Combine like terms: 12x + -12x = 0 5 + -1x = 0 Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| -4+5a=-31 | | 0+1.2(x)=9.9+-1.2(x) | | b+5=1+5b | | 2+3=8-3 | | 5x=25y | | x/12-8=5/24 | | 0.75/9 | | 9(x+1)+2=-2(x-3)-10 | | 5x-16=3(10-x) | | x/8-5=3/16 | | 27h+.99=42.72 | | 2tanxcos*x-1=0 | | 2w-3=3w | | 5/4=45/x | | h-48/g | | 132.49+15w=192.49 | | 17a-2b+3c=-107 | | 15-0.33y=x+17 | | 5x-165=45-2x | | 6y+(-5)=(-23) | | -8/3*-2 | | 4m-4=2(2m) | | a=-16+3b+-2c | | 5(h+3)+2(h-2)=11-3(12-5h) | | 2(m-3)=8 | | Y-5=-8/3(x-2) | | 9+2v=-v | | Y=65x+0.10 | | 2.464cosx-x=2.5843 | | 7x+9=3x+8 | | -a/10=-16 | | a-3b+2c=-16 |